Analisis Retribusi dan Pengaruhnya Terhadap Kemandirian Pembangunan Daerah - Dadang Sudirno; Hani Sri Mulyani2 (ITB AAS INDONESIA, 2021)
Independence of Regional Development in regional autonomy is the ability of local governments to self-finance government activities, development, services to the community and manage regional finances, especially Regional Original Income (PAD) and Economic Growth Levels without relying mostly on assistance from the central government. This study aims to determine the effect of local taxes, levies and the level of economic growth on the independence of regional development in CIAYUMAJAKUNING regencies / cities for the 2011-2018 period, either partially or simultaneously. The variables used in this study are Local Taxes, Retribution, Economic Growth Rate and Regional Development Independent Ratio obtained from the website of the Directorate General of Financial Balance (DJPK) and the website of the Regency / City Central Statistics Agency (BPS) in West Java. The analytical method used is descriptive analysis method and verification. The sample selection in this study used the saturated sample method, and the samples from this study were 5 districts / cities, namely Cirebon City, Cirebon Regency, Majalengka Regency, Indramayu Regency and Kuningan Regency in the 2011-2018 period so that 40 sample data were obtained. The analytical tool used in this research is simple linear regression analysis. The results of this study indicate that Retribution has a significant effect on the Independence of Regional Development.